The Use of Plant Origin Remedies in Children with ARVI - O. V. Shamsheva (LLC "Diagnostics and Vaccines", 2018)
The analysis of the scientific literature and the results of clinical studies on the safety and efficacy of using for respiratory infections components of plant origin and bee products included in the composition of biologically active food supplements - «Propolis with Herbs» marmalade, throat lollipop with honey and Althaea night syrup with honey-line INVAR KIDS. It has been shown that the use of herbal remedies that contain components with established clinical safety and proven efficacy as a symptomatic therapy is reasonable for alleviating the main symptoms of respiratory diseases in children.